LEVEL OF AWARENESS, ACCESS AND USE OF LONG LASTING INSECTICIDAL NETS (LLINs) IN FIVE PUBLIC HEALTH CENTRES WITHIN KADUNA METROPOLIS - YAYOCK, HOSEA; Osageide, N. O.; Mande, H.; Habib, H.; Zamani, I. (FUDMA JOURNAL OF SCIENCES, 2020)
A cross sectional study designed to assess the difference in level of Awareness, Access and Use of Long Lasting Insecticidal Nets (LLINs) from consenting pregnant women aged between 15 to 40 years attending routine ante-natal clinic sessions at Kaduna State University (Barau Dikko) Teaching Hospital, General Hospital Kawo, Primary Health Care Badarawa, Primary Health Care Angwan Romi and General Hospital Sabon Tasha. A total of 360 questionnaires were distributed, but only 308 returned completed. Also, mosquito samples were collected in 30 randomly selected households of the consenting pregnant women that were within three kilometer radius range of the antenatal clinic for 12 weeks’ period. A one-way ANOVA was conducted using SPSS statistical package version 22. The result revealed that there was no significant difference (P> 0.05) in level of Awareness (92.53%), Access (75.32%) and Use (67.86%) of Long Lasting Insecticidal Nets (LLINs) among the pregnant women attending the various ante-natal hospitals/primary health care facilities. A total of 344 larvae samples were encountered and identified as Culex species 259(75.29%) and Aedes species 85(24.71%). Awareness, Access and Use of LLINs is relatively similar; while the mosquito species are vectors of Filariasis, Yellow fever, Dengue fever and can be prevented by the use of LLINs. ______________________________________________________________________________ Key word: Kaduna Metropolis, LLINs Awareness, Access and Use, Mosquito Preventive